Competitive personalized pricing - Zhijun Chen; Chongwoo Choe; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2018)
We study a duopoly model where each firm chooses personalized prices for its targeted consumers, who can be active or passive in identity management. Active consumers can bypass price discrimination and have access to the price offered to non-targeted consumers, which passive consumers cannot. When all consumers are passive, personalized pricing leads to intense competition and total industry profit lower than that under the Hotelling equilibrium. But market is always fully covered. Active consumers raise the firm's cost of serving non-targeted consumers, which softens competition. When firms have sufficiently large and non-overlapping target segments, active consumers enable firms to extract full surplus from their targeted consumers through perfect price discrimination. With active consumers, firms also choose not to serve the entire market when the commonly non-targeted market segment is small. Thus active identity management can lead to lower consumer surplus and lower social welfare. We also discuss the regulatory implications for the use of consumer information by firms as well as the implications for management.
Keywords: D43; D8; L13; L5; 330; Personalized pricing; identity management; customer targeting